Draft Annual Plan 1988-89 Volume : IX Hill Areas Government of Assam - Planning Commission (Planning Commission, 1988)
Construction of Roads in the two Hill Districts to Sub-serve the need of the H.P.C. for transportation of their raw material there from is in progress. The alignments of such roads are based on best consideration of the concept of maximum benefit and minimum cost and also ensuring least interference with soil structure as well as the ecology. The cost estimate, showing different estimated cost per Km. are due to the different ground conditions/Rock structures etc. and these estimates were based an actual condition at sites.
Government of Assam, Development Commissioner for Hill Areas